Effect of Some Chemicals & Bio-Treatments on Post-Harvest Quality of Persimmon Fruits (Diospyros kaki L.) cv. "Hachyia" (Journal of Hama University, 2019)
Many chemical and Bio-treatments  were used pre and post-harvest of fruits which  harvested  after foliar spraying its trees by Yeast extract with two concentrations (4 , 8 g/L) and EM 1 with two concentations (3,4 ml/L) ,while Calcium Carbide with two concentrations (2,3 g/Kg fruits) was used only post-harvest and the fruits of control (immersed in water). The experiment was observed during season 2017 and its effect on fruit quality of persimmon cv. Hachyia was studied.The results showed that packing fruits after foliar spraying its trees by Yeast extract with concentration (8 g/L) was higher with significant differences in  Fruit Weight , length , diameter , Vitamin C and Reducing Sugars (230 g , 6.83 cm , 7.38 cm, 50.43 mg/100  g fresh weight, 8.33 %) recpectivly compard with the control (131.9 g , 5.38 cm , 6.06 cm , 15.3 mg/100 g fresh wieght , 6%) recpectivly , In addition a significant decrease in totall acidity  was observed in Calcium Carbide treatments with two concentations(2,3 g/Kg Fruits) & packing fruits treatment after foliar spraying its trees by EM1 with concentration (4 ml/L) that reach to (0.36 %) comparing with control (0.62 %).